Limosilactobacillus reuteri administration alters the gut-brain-behavior axis in a sex-dependent manner in socially monogamous prairie voles - Donovan, Meghan; Mackey, Calvin S.; Lynch, Michael D. J.; Platt, Grayson N.; Brown, Amber N.; Washburn, Brian K.; Trickey, Darryl J.; Curtis, J. Thomas; Liu, Yan; Charles, Trevor C.; Wang, Zuoxin; Jones, Kathryn M. (Frontiers in Microbiology, 2023)
Research on the role of gut microbiota in behavior has grown dramatically. The probiotic L. reuteri can alter social and stress-related behaviors – yet, the underlying mechanisms remain largely unknown. Although traditional laboratory rodents provide a foundation for examining the role of L. reuteri on the gut-brain axis, they do not naturally display a wide variety of social behaviors. Using the highly-social, monogamous prairie vole (Microtus ochrogaster), we examined the effects of L. reuteri administration on behaviors, neurochemical marker expression, and gut-microbiome composition. Females, but not males, treated with live L. reuteri displayed lower levels of social affiliation compared to those treated with heat-killed L. reuteri. Overall, females displayed a lower level of anxiety-like behaviors than males. Live L. reuteri-treated females had lower expression of corticotrophin releasing factor (CRF) and CRF type-2-receptor in the nucleus accumbens, and lower vasopressin 1a-receptor in the paraventricular nucleus of the hypothalamus (PVN), but increased CRF in the PVN. There were both baseline sex differences and sex-by-treatment differences in gut microbiome composition. Live L. reuteri increased the abundance of several taxa, including Enterobacteriaceae, Lachnospiraceae NK4A136, and Treponema. Interestingly, heat-killed L. reuteri increased abundance of the beneficial taxa Bifidobacteriaceae and Blautia. There were significant correlations between changes in microbiota, brain neurochemical markers, and behaviors. Our data indicate that L. reuteri impacts gut microbiota, gut-brain axis and behaviors in a sex-specific manner in socially-monogamous prairie voles. This demonstrates the utility of the prairie vole model for further examining causal impacts of microbiome on brain and behavior.